Requirements for Multicultural Competencies Defined by a Focus Group - Lázár, Tímea; Bene, Ágnes (International Journal of Engineering and Management Sciences, 2018)
Globalization, the spread of multinational companies and the enormous development of information technology can lead to a new trend in employers’ requirements. However, being employed by an international company is a real possibility for any employee in any part of the world. Even if they do not have to work abroad, employees may have to function in a multinational environment in their home countries. A favourable combination of intercultural competencies is a key factor in the selection and development of employees. A possible way of measuring these competencies can be the Multicultural Personality Questionnaire (MPQ). First of all,on the employers’ part, it is important to clarify the exact requirements and competencies (dimensions) to be able to draw up an ‘ideal profile’. We prepared two versions of the MPQ (91-item; 5-dimensional) and used them to test employers’ requirements in the selection process regarding the dimensions of cultural empathy, open-mindedness, social initiative, emotional stability and flexibility. This study describes the results of a focus group interview, which took place in 2017, revealing the importance of multicultural competencies from the employers’ point of view and examining the conditions of the adaptability of the two questionnaires. We used the focus group method to find out in what conditions the questionnaires canbe used in a selection process. What possibilities and limits are therefor using the direct five-dimensional questionnaire? What aspects do we need to take into consideration in expressing and interpreting the requirements in the results of the test?